Outcome of lung oligometastatic patients treated with stereotactic body irradiation - Virbel, Guillaume; Cox, David G.; Olland, Anne; Falcoz, Pierre-Emmanuel; Le Fevre, Clara; Schott, Roland; Antoni, Delphine; Noel, Georges (Frontiers in Oncology, 2022)
Purpose The oligometastatic stage is an intermediate stage of cancer between the localized stage and polymetastatic stage. The prognosis of patients in this stage also appears to be intermediate. Lung stereotactic body radiotherapy is a possible tool for treating oligometastatic lung sites. The objective of our study was to evaluate the clinical outcomes in terms of local control, progression-free survival, overall survival, and toxicity of SBRT in oligometastatic patients with lung metastases from any solid primary tumor. Materials and methods Clinical records of consecutive lung oligometastatic patients treated between January 2010 and December 2020 for lung SBRT at 60 Gy in 3- or 8-fraction schedules and a controlled primary tumor were retrospectively analyzed. Results After a median follow-up of 20.3 months, local failure occurred for 14 lesions, 57 patients experienced lung progression, and 64 patients experienced disease progression. Overall survival rates at 1 and 2 years were 85.6 and 69.7%, respectively. Fifty-two patients experienced radiation pneumonitis, but only 2 patients were symptomatic and presented grade 2 late pneumonitis. No grade 3-4 toxicity was observed. ECOG 0 was the only prognostic factor for overall survival (HR = 3.5; 95% CI 3.2-3.8; p < 0.01). Conclusion SBRT with a 60-Gy schedule in 8 fractions is an effective and well-tolerated treatment for patients with lung oligometastases from any solid primary tumor.